Predictors of perceived stigmatization in patients with psoriasis. (22nd December 2016) - van Beugen, S.; van Middendorp, H.; Ferwerda, M.; Smit, J.V.; Zeeuwen‐Franssen, M.E.J.; Kroft, E.B.M.; de Jong, E.M.G.J.; Donders, A.R.T.; van de Kerkhof, P.C.M.; Evers, A.W.M.
Abstract : What's already known about this topic? Perceived stigmatization is common and distressing in patients with psoriasis. Some of its predictors have been examined in small samples. What does this study add? This large study of 514 patients with psoriasis examined a combination of potential predictor variables, both previously examined and never before studied. Sociodemographic, disease‐related and previously unstudied type D personality variables were found to be predictive of perceived stigmatization. What are the clinical implications of this work? These results provide an understanding of which patients may be especially vulnerable to stigmatization‐related problems, which may warrant special attention during treatment. Summary: Background: The physical appearance of psoriasis can be cosmetically disfiguring, resulting in a substantial social burden for patients. An important aspect of this burden is the experience of stigmatization. While stigmatization is known to be disabling and stressful for patients, little is known about its correlates, and effective interventions are lacking. Objectives: To examine predictor variables for perceived stigmatization in psoriasis. Methods: Questionnaires were administered to 514 patients with psoriasis in a cross‐sectional study. Zero‐order correlation and multiple‐regression analyses were conducted including sociodemographic, disease‐related, personality, illness cognitions and social support predictor variables. Results: Stigmatization was experienced by 73% of patients to some degree, and correlated with all five categories of predictor variables. In multiple‐regression analyses, stigmatization was associated with higher impact on daily life; lower education; higher disease visibility, severity and duration; higher levels of social inhibition; having a type D personality; and not having a partner. Conclusions: The results indicate that perceived stigmatization is common in psoriasis, and can be predicted by sociodemographic, disease‐related and personality variables. These predictor variables provide indications of which patients are especially vulnerable regarding perceived stigmatization, which might be used in treatment.